METHODS AND METHODS OF TEACHING IN LABOR EDUCATION - Kholmatova Mashkhura Anvarovna; Tursunov Farhad Ermakbaevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
this scientific article uses various methods of teaching in labor education. It is covered that the choice of educational methods depends primarily on the nature of the educational material and educational tasks.